2021
DOI: 10.3390/biom12010059
|View full text |Cite
|
Sign up to set email alerts
|

The Functional Differences between the GroEL Chaperonin of Escherichia coli and the HtpB Chaperonin of Legionella pneumophila Can Be Mapped to Specific Amino Acid Residues

Abstract: Group I chaperonins are a highly conserved family of essential proteins that self-assemble into molecular nanoboxes that mediate the folding of cytoplasmic proteins in bacteria and organelles. GroEL, the chaperonin of Escherichia coli, is the archetype of the family. Protein folding-independent functions have been described for numerous chaperonins, including HtpB, the chaperonin of the bacterial pathogen Legionella pneumophila. Several protein folding-independent functions attributed to HtpB are not shared by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 62 publications
(83 reference statements)
0
2
0
Order By: Relevance
“…However, it showed less than 70% nucleotide identity, and the actual gene annotated by Prokka was groL , which encodes a chaperonin GroEL. According to Valenzuela‐Valderas et al, GroEL in Escherichia coli differs by several amino acids from HtpB in Legionella pneumophila (the reference species for htpB in the VFDB), leading to a functionally different protein folding that may not be conducive to infection (Valenzuela‐Valderas et al, 2022 ). Therefore, it is not expected to be virulent and has only been reported to be immunogenic in Flavobacterium (Liu et al, 2012 ; Valenzuela‐Valderas et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…However, it showed less than 70% nucleotide identity, and the actual gene annotated by Prokka was groL , which encodes a chaperonin GroEL. According to Valenzuela‐Valderas et al, GroEL in Escherichia coli differs by several amino acids from HtpB in Legionella pneumophila (the reference species for htpB in the VFDB), leading to a functionally different protein folding that may not be conducive to infection (Valenzuela‐Valderas et al, 2022 ). Therefore, it is not expected to be virulent and has only been reported to be immunogenic in Flavobacterium (Liu et al, 2012 ; Valenzuela‐Valderas et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…HtpB encodes a chaperone protein known to modify eukaryotic cell signaling pathways, facilitating the entry of bacteria into the mammalian cytoplasm. This capability enhances bacterial replication within host cells [ 32 ]. The identification of the htpB gene in the Legionellosis pathway strongly suggests that the P. multocida SHZ01 strain may employ this gene to communicate with host cells.…”
Section: Discussionmentioning
confidence: 99%
“…Valenzuela-Valderas et al [11] compared the primary structures of GroEL and HtpB and were successful in demonstrating that at least 10 amino acid residues were important for the interaction of HtpB with the eukaryotic proteasome-related protein ECM29. Using Evolutionary Trace Analysis, the authors identified and mutated amino acid residues potentially involved in the protein-folding-independent functions of HtpB.…”
mentioning
confidence: 99%